Heat insulation material
The heat insulating material, featuring a silica particle-based thermal insulation layer and an inorganic fiber buffer layer, addresses the lack of burst resistance in existing materials by providing effective flame and wind pressure resistance, ensuring reliable thermal insulation even in the event of cell bursts.
Patent Information
- Application Number
- JP2023173144
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-04
- Publication Date
- 2025-04-16
AI Technical Summary
Existing heat insulation materials for battery modules and packs lack sufficient burst resistance, which is essential to prevent heat propagation and thermal runaways in case of abnormal cell heating or bursting.
A heat insulating material comprising a thermal insulation layer with silica particles and a buffer layer made of inorganic fibers, providing both flame resistance and wind pressure resistance, even when subjected to local high heat or wind pressure due to cell bursts.
The material effectively maintains its insulation function and prevents damage, ensuring the reliability of battery modules by withstanding bursts and maintaining thermal insulation under extreme conditions.
Smart Images

Figure 2025063723000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a thermal insulation material. [Background technology]
[0002] The use of non-aqueous electrolyte secondary batteries such as lithium-ion batteries as power sources for electric vehicles such as electric vehicles (EVs), hybrid vehicles (HEVs), plug-in hybrid vehicles (PEVs), and fuel cell vehicles (FCVs) is progressing. In these applications, non-aqueous electrolyte secondary batteries are usually used in the form of a battery module or battery pack including a battery assembly by integrating a plurality of battery cells (single cells) to obtain high output and capacity as a power source. In this case, adjacent cells are not directly contacted with each other, and a heat insulating material for insulating the cells may be placed between the cells. For example, Patent Document 1 describes a heat insulating sheet that is interposed between battery cells of a battery assembly and includes first particles composed of silica particles, second particles composed of titania or the like, and a binder such as organic fiber or inorganic fiber. Patent Document 2 is another technical document related to heat insulating materials. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent Publication No. 2021-34278 [Patent Document 2] International Publication No. 2023 / 054411 Summary of the Invention [Problem to be solved by the invention]
[0004] A heat insulating material used in a battery module or battery pack (hereinafter, collectively referred to as "battery module, etc.") of a non-aqueous electrolyte secondary battery may be required to have a function of preventing, for example, when some cells abnormally generate heat, the heat from being transmitted to other cells and causing thermal runaway. For this reason, it is desirable for the heat insulating material to have high heat resistance in addition to high heat insulating properties. However, when a cell abnormally generates heat, the load applied to the heat insulating material arranged between the cell and an adjacent cell is not limited to heat transfer from the outer surface of the cell that generated heat. For example, when a cell that abnormally generates heat bursts due to an increase in internal pressure, the heat insulating material adjacent to the cell may be subjected to local wind pressure due to gas ejected from the cell, or local high heat due to ejection or scattering of contents. If a heat insulating material having the performance (burst resistance) capable of properly maintaining the heat insulating function even when such a burst occurs is provided, it would be beneficial from the viewpoint of improving the reliability of the battery module, etc.
[0005] Therefore, an object of the present invention is to provide a heat insulating material whose heat insulating function is not easily deteriorated even if an adjacent cell bursts. [Means for solving the problem]
[0006] The heat insulating material provided by this specification includes a heat insulating layer and a buffer layer. The heat insulating layer includes silica particles. The buffer layer is a fiber molded body mainly composed of inorganic fibers. The heat insulating material is in a sheet shape having a first surface and a second surface, and each of the first surface and the second surface is composed of the heat insulating layer or the buffer layer. The heat insulating material has flame resistance that is evaluated as passing in the following burner test, regardless of whether the first surface or the second surface is the surface to be evaluated. [Burner test] The surface to be evaluated of the insulation material is heated to 750° C. for 2 minutes using a burner, and if no through holes are formed in the layer that constitutes the surface to be evaluated, it is rated as "passed."
[0007] The insulating material includes the insulating layer and the buffer layer in combination, and thus, during normal use, the insulating property and the compressive deformability capable of appropriately buffering the stress that may occur due to the expansion of the cell (for example, the expansion due to charging) can be easily balanced. In addition, according to the above configuration, even when the insulating material is subjected to local wind pressure, the buffer layer can protect or support the insulating layer, and the performance of the insulating material can be prevented from deteriorating by preventing damage to the insulating layer (for example, preventing the occurrence of through holes). In addition, since both the first and second surfaces of the insulating material have a level of flame resistance that passes the burner test described above, the performance of the insulating material can be suppressed from deteriorating even when local high heat is applied. Therefore, the insulating material can have the performance (burst resistance) to appropriately maintain its insulating function even if local wind pressure or high heat is applied due to the burst of an adjacent cell.
[0008] In some embodiments, the heat insulating material may have one of the first surface and the second surface constituted by the heat insulating layer, and the other surface constituted by the buffer layer. When the heat insulating material is implemented in a minimum configuration, the number of the heat insulating layer and the number of the buffer layer can be only one, so that the heat insulating material is suitable for thinning.
[0009] In some preferred embodiments, the insulating material has wind pressure resistance that is evaluated as pass in the following air blow test, regardless of whether the first surface or the second surface is the surface to be evaluated. An insulating material that satisfies the following wind pressure resistance in addition to the above flame resistance can exhibit better burst resistance. [Air blow test] Air at a flow rate of 940 L / min is sprayed from a nozzle with a diameter of 6 mm for 60 seconds from a position 10 mm in the normal direction of the surface of the insulation being evaluated, and if no through holes are formed in the layer that makes up the surface being evaluated, it is rated as "passed."
[0010] In some embodiments, the insulating layer preferably contains fumed silica as the silica particles. The insulating material disclosed herein can be preferably implemented in an embodiment including an insulating layer containing fumed silica and inorganic fibers.
[0011] In some embodiments, the buffer layer may contain, as a main component, one or more inorganic fibers selected from the group consisting of alkali metal silicate fibers, silica-alumina ceramic fibers, and alumina fibers.
[0012] The heat insulating material disclosed herein can be embodied, for example, in an embodiment in which the initial thickness of the heat insulating material is 5 mm or less. A heat insulating material having such a limited thickness is preferable from the viewpoint of miniaturization and high energy density of a battery module or the like.
[0013] In some embodiments, the insulating material preferably has a compressive deformation rate of 10% or more at a compressive stress of 0.4 MPa. An insulating material exhibiting such compressive properties can appropriately absorb stress that may be generated by cell expansion, and can prevent excessive pressure from being applied to the cells.
[0014] The heat insulating material disclosed herein may be used in a form in which the heat insulating material is covered with a coating material (a form of a heat insulating material with a coating material). From the viewpoint of avoiding a significant loss of the compression characteristics of the heat insulating material, in some embodiments, it is preferable that the coating material is made of a resin film.
[0015] The heat insulating material disclosed herein can be used by being disposed between adjacent cells in a battery module or battery pack including a plurality of arranged cells. For example, taking advantage of its characteristic of exhibiting good burst resistance, the heat insulating material can be preferably used as a heat insulating material disposed between adjacent cells in a battery module or battery pack for vehicle use (for example, used as a driving power source for a vehicle).
[0016] In addition, any suitable combination of the elements described in this specification may also be included within the scope of the invention for which patent protection is sought by this patent application. [Brief description of the drawings]
[0017] [Figure 1] FIG. 2 is a perspective view illustrating an example of a battery module having a thermal insulator disposed between cells according to an embodiment. [Diagram 2] FIG. 2 is a cross-sectional view taken along line II-II of FIG. [Diagram 3] FIG. 1 is a cross-sectional view showing a schematic diagram of a heat insulating material according to one embodiment. [Figure 4] FIG. 2 is a schematic diagram for explaining a burner test. [Diagram 5] FIG. 1 is a schematic diagram for explaining an air blow test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] A preferred embodiment of the present invention will be described below. Note that matters other than those specifically mentioned in this specification and necessary for carrying out the present invention can be understood by a person skilled in the art based on the teachings on carrying out the invention described in this specification and the common general knowledge at the time of filing. The present invention can be carried out based on the contents disclosed in this specification and the common general knowledge in the field. In addition, in the following drawings, components and parts having the same function may be described by using the same reference numerals, and duplicated descriptions may be omitted or simplified. In addition, the embodiments described in the drawings are schematic in order to clearly explain the present invention, and do not necessarily accurately represent the size or scale of the product actually provided.
[0019] <Thermal insulation layer> (Silica particles) The heat insulating material disclosed herein has a heat insulating layer containing silica particles. Silica (SiO2) can be classified into crystalline silica, amorphous silica, etc. based on structural characteristics, and can be classified into natural silica, synthetic silica, etc. based on the method of acquisition. Synthetic silica can be classified into dry silica, wet silica, silica aerogel, etc. based on the manufacturing method. Dry silica can be classified into silica obtained by a combustion method, silica obtained by an arc method, etc., and wet silica can be classified into silica obtained by a gel method, silica obtained by a precipitation method, etc. The type of silica particles used as a component of the heat insulating layer is not particularly limited, and may be any of the above-mentioned types of silica particles. In some embodiments, dry silica is preferred, and among dry silica, fumed silica is more preferred, and among fumed silica, hydrophilic fumed silica is particularly preferred. Note that hydrophilic fumed silica refers to fumed silica that mainly has hydrophilic silanol groups (Si-OH) on the surface, and generally refers to fumed silica in which the silanol groups have not been replaced with hydrophobic groups by surface treatment or the like.
[0020] Silica particles generally exist as primary particles, as aggregates of primary particles, or as aggregates of aggregates of primary particles. The silica particles in the heat insulating layer may be dispersed in the form of primary particles, aggregates, aggregates, or a combination of these.
[0021] The average primary particle diameter of the silica particles is not particularly limited, and is, for example, about 1 nm to 100 nm, preferably 2 nm or more, more preferably 4 nm or more, and preferably 80 nm or less, more preferably 40 nm or less, more preferably 30 nm or less, and particularly preferably 20 nm or less. When the silica particles contain fumed silica, the average primary particle diameter of the fumed silica is, for example, about 1 nm to 40 nm, preferably 2 nm or more, more preferably 4 nm or more, and preferably 30 nm or less, more preferably 20 nm or less, and more preferably 18 nm or less. When the average primary particle diameter of the silica particles is within the above range, good heat insulation is easily ensured. In addition, as a method for grasping the average primary particle diameter of the silica particles, a method of measuring using an electron microscope such as a scanning electron microscope (SEM) or a transmission electron microscope (TEM) can be mentioned. Specifically, a method of randomly selecting silica particles reflected in the electron microscope, measuring the particle diameter, and calculating the average value of the numerical values can be mentioned. The particle size may be, for example, the diameter of a spherical particle, the midpoint between its short axis and long axis when the particle is elliptical as viewed under an electron microscope, or the midpoint between its short side and long side when the particle is an irregular particle.
[0022] The average particle size of the secondary aggregates of silica particles (aggregates of primary particles) is not particularly limited and is usually 0.1 μm to 100 μm, but is preferably 1 μm or more, more preferably 2 μm or more, and preferably 90 μm or less, more preferably 80 μm or less. The average particle size of the secondary aggregates of silica particles can be determined by measuring it in the same manner as the primary particle size.
[0023] The BET specific surface area of the silica particles is not particularly limited, and is, for example, 40 m 2 / g or more 800m 2 / g or less, and 2 / g or more 600m 2 In some embodiments, the BET specific surface area of the silica particles may be about 90 m 2 / g or more 380m 2 / g, preferably less than 130m 2 / g or more, more preferably 175m 2 / g or more, more preferably 200m 2 / g or more, and preferably 350m 2 / g or less, more preferably 320m 2 / g or less, more preferably 300m 2 / g or less. When the BET specific surface area of the silica particles is within the above range, good heat insulation can be easily ensured even under high temperature and high humidity conditions. The BET specific surface area can be measured by a multipoint nitrogen adsorption method (BET method) in accordance with the International Organization for Standardization ISO 5794 / 1. For example, Aerosil 380 has a nominal BET specific surface area of 380 m. 2 / g, taking into account the error, it is 350m 2 / g~410m 2 In this case, the nominal value of 380m 2 / g shall be considered as the standard.
[0024] The apparent density of the silica particles is not particularly limited, and may be, for example, 30 g / L to 130 g / L, preferably 40 g / L or more (for example, 50 g / L or more), and preferably 120 g / L or less (for example, 100 g / L or less). In some embodiments, the apparent density of the silica particles may be, for example, 80 g / L or less, or 60 g / L or less. The apparent density of the silica particles can be determined by filling the silica particles into a container capable of measuring the volume, such as a 250 mL graduated cylinder, measuring the filling mass (Xg) and filling volume (YmL) of the silica particles, and dividing the filling mass by the filling volume ([apparent density (g / L)]=X / Y×1000). In addition, when a nominal value of the apparent density is provided by a manufacturer or the like, the nominal value can be adopted.
[0025] Examples of commercially available silica particles include hydrophilic fumed silica AEROSIL series (manufactured by Nippon Aerosil Co., Ltd.) AEROSIL 50, 90, 130, 200, 200V, 300, 380, Reolosil series (manufactured by Tokuyama Corporation) QS-09, QS-10, QS-102, QS-20, QS-20L, QS-30, QS-40, CP-102, HDK series (manufactured by Wacker Asahi Kasei Silicone Co., Ltd.) HDKV15, N20, T30, T40, etc., hydrophobic fumed silica AEROSIL series (manufactured by Nippon Aerosil Co., Ltd.) AEROSIL R972, R976S, HDK series (manufactured by Wacker Asahi Kasei Silicone Co., Ltd.) HDK H15, H20, H30, etc., silica aerogel Airica (manufactured by Tokuyama Corporation), etc. The heat insulating layer may contain one type of silica particles, or may contain two or more types of silica particles.
[0026] The content of silica particles in the heat insulating layer is not particularly limited, and may be, for example, within the range of 50% by mass to 99.5% by mass. In some embodiments, the content is preferably 60% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, and is preferably 95% by mass or less, more preferably 90% by mass or less, even more preferably 85% by mass or less. When the content of silica particles is within any of the above ranges, the heat insulating layer can easily ensure good heat insulation, and the heat insulating material including the heat insulating layer and the buffer layer can easily ensure good wind pressure resistance.
[0027] (Inorganic fiber) In some preferred embodiments, the heat insulating layer contains inorganic fibers in addition to silica particles. The inorganic fibers can be useful for improving the ease of manufacture (e.g., ease of molding) of the heat insulating layer containing silica particles, improving the thickness accuracy, and improving the strength of the heat insulating layer. The type of inorganic fibers is not particularly limited. Examples of inorganic fibers that can be preferably used from the viewpoint of heat resistance and strength include glass fibers, silica fibers, alumina fibers, silica-alumina fibers, silica-alumina-magnesia fibers, biosoluble inorganic fibers, zirconia fibers, alkaline earth metal silicate (alkaline earth silicate (AES)) fibers, glass wool, rock wool, and basalt fibers. The heat insulating layer may contain one type of inorganic fiber, or may contain two or more types of inorganic fibers.
[0028] The content of inorganic fibers in the heat insulating layer is not particularly limited and may be, for example, 0.5% by mass to 50% by mass, and is preferably 1% by mass or more, more preferably 3% by mass or more, and even more preferably 5% by mass or more, and is preferably 40% by mass or less, more preferably 35% by mass or less, and even more preferably 30% by mass or less. When the fiber content is within the above range, it is easy to ensure good heat resistance and to manufacture the heat insulating layer.
[0029] The average fiber length of the inorganic fibers is not particularly limited and may be, for example, 0.05 mm to 50 mm, preferably 0.5 mm or more, more preferably 1.0 mm or more, and even more preferably 2 mm or more, and is preferably 25 mm or less, more preferably 13 mm or less, and even more preferably 10 mm or less, and may be 8 mm or less, or may be 6 mm or less. When the average fiber length of the fibers is within the above range, it is easy to favorably achieve both ease of manufacture and strength of the heat insulating layer.
[0030] The average fiber diameter of the inorganic fibers is not particularly limited and may be, for example, 0.1 μm to 50 μm, and is preferably 1 μm or more, more preferably 5 μm or more, and even more preferably 7 μm or more, and is preferably 25 μm or less, more preferably 20 μm or less, and even more preferably 15 μm or less. When the average fiber diameter of the fibers is within the above range, good thermal insulation properties and mechanical strength are easily ensured.
[0031] In some embodiments, the inorganic fibers preferably include inorganic fibers having a fiber length of 6 mm or more and less than 35 mm. The proportion of inorganic fibers having a fiber length of 6 mm or more and less than 35 mm in the total number of inorganic fibers contained in the heat insulating layer is not particularly limited, and may be, for example, 30% to 100%, preferably 95% or less, preferably 35% or more, more preferably 40% or more, and even more preferably 50% or more. When the content ratio of inorganic fibers having the above fiber length is within the above range, good heat insulating properties and mechanical strength are easily ensured.
[0032] In an embodiment in which the heat insulating layer contains inorganic fibers, the mass ratio of the silica particles and inorganic fibers contained in the heat insulating layer (silica particles: inorganic fibers) is not particularly limited, and may be, for example, within the range of 40:60 to 99: 1. From the viewpoint of easily ensuring a good balance between good heat insulating properties and mechanical strength, in some embodiments, the mass ratio (silica particles: inorganic fibers) is, for example, suitably 45:55 or more, preferably 50:50 or more, more preferably 60:40 or more, even more preferably 70:30 or more, and may be 80:20 or more (for example, 82:18 or more), and may be, for example, suitably 98:2 or less, preferably 95:5 or less, may be 90:10 or less, or may be 88:12 or less.
[0033] (Dispersant) The heat insulating layer may contain a dispersant as an optional component. For example, when the heat insulating layer is produced using a mixed liquid containing the constituent materials of the heat insulating layer in a solvent, the dispersant can be useful for improving the ease of preparation of the mixed liquid, improving the handleability (e.g., improving fluidity), improving the dispersion stability (e.g., suppressing viscosity change over time), and improving the moldability when forming the heat insulating layer from the mixed liquid. An example of an embodiment in which the use of a dispersant is preferable is an embodiment in which a protic solvent is used as the solvent for the mixed liquid. For example, in an embodiment in which hydrophilic fumed silica is used as at least a part of the inorganic particles, the hydrophilic fumed silica and the protic solvent are bonded by hydrogen bonds, so that the viscosity of the mixed liquid is likely to increase. In addition, when the specific surface area of the inorganic particles (e.g., silica particles such as hydrophilic fumed silica) is high, the area that interacts with the solvent is widened, so that the viscosity of the mixed liquid tends to increase. If the viscosity of the mixed liquid becomes excessively high, there is a concern that the mixing itself becomes difficult, leading to a decrease in productivity and a decrease in quality stability. A dispersant can be used to prevent such an event. In addition, in a mode in which the heat insulating layer contains inorganic fibers, it is preferable to suppress an excessive increase in viscosity of the mixed liquid from the viewpoint of preventing damage to the inorganic fibers during the manufacturing process.
[0034] The dispersant is not particularly limited, and a material capable of exerting the desired effect can be appropriately selected and used. Dispersants may be classified as follows: 1) polymeric dispersants, 2) surfactant-type dispersants (low molecular weight dispersants), 3) inorganic dispersants, etc. From the viewpoint of suppressing the decrease in the consistency of the mixed liquid and suppressing the aggregation of inorganic particles, etc., in some embodiments, a non-polymeric dispersant may be preferably used. Here, "non-polymeric" means a molecule that does not contain a polymer (polymer) generated by a polymerization reaction in its structure, that is, a so-called "low molecular weight compound". A suitable example of a non-polymeric dispersant is a surfactant. Surfactants are classified into anionic surfactants, nonionic surfactants, cationic surfactants, and amphoteric surfactants. The surfactants can be used alone or in appropriate combination of two or more types. In some embodiments, cationic or nonionic surfactants can be preferably used. For example, so-called quaternary ammonium salt type surfactants, amine salt type surfactants, pyridium salt type surfactants, amine type surfactants, etc. are preferable. As a suitable example, a compound having at least one alkyl group having 4 or more carbon atoms (preferably 8 or more) on a nitrogen atom (for example, quaternary ammonium salt type surfactants such as dodecyltrimethylammonium chloride, octadecyltrimethylammonium chloride, dodecylbenzyldimethylammonium chloride salt, etc.; amine salt type surfactants such as tetradecylamine acetate, octadecylamine acetate, etc.; amine type surfactants such as dodecylamine, octyldimethylamine, etc.) can be preferably used as a non-polymeric dispersant. The non-polymeric dispersant in the heat insulating layer may be present in the form of a salt, or in the form of a free compound or ion. Examples of the above salt include quaternary ammonium salts with counter ions such as chloride ions, bromide ions, ethyl sulfate ions, etc., and amine salts with acetic acid.
[0035] The content of the dispersant (e.g., non-polymeric dispersant) in the heat insulating layer is not particularly limited. The content of the dispersant is typically more than 0% by mass, and may be, for example, 0.0001% by mass or more, 0.0005% by mass or more, 0.001% by mass or more, or 0.05% by mass or more. The content of the dispersant in the heat insulating layer may be, for example, 7% by mass or less, and is usually 5% by mass or less (e.g., 0.0001% by mass or more and 5% by mass or less) from the viewpoint of easily suppressing the influence on other properties. In some embodiments, the content of the dispersant in the heat insulating layer is, for example, about 0.01% by mass to 5% by mass, preferably 0.05% by mass or more, more preferably 0.1% by mass or more, even more preferably 0.2% by mass or more, and also preferably 3% by mass or less, more preferably 2% by mass or less, even more preferably 1% by mass or less, particularly preferably 0.5% by mass or less, and may be 0.3% by mass or less, 0.1% by mass or less, 0.05% by mass or less, 0.01% by mass or less, 0.005% by mass or less, 0.001% by mass or less, or 0.0005% by mass or less. The content of the dispersant in the heat insulating layer can be obtained by extracting the dispersant from the heat insulating layer using an appropriate solvent (a solvent capable of dissolving the target dispersant) and performing quantitative analysis by a known method. The type of dispersant contained in the heat insulating layer can be grasped by extracting the dispersant from the heat insulating layer using an appropriate solvent in the same manner as above, and identifying the dispersant contained in the obtained extract by a known method. The dispersant contained in the heat insulating layer can be considered to be the remaining amount of the dispersant used during the production of the heat insulating material.
[0036] (Other Ingredients) The heat insulating layer may contain other components as necessary in addition to those described above. Specific examples of the other components include a binder (binding agent), inorganic particles other than silica particles, and organic fibers.
[0037] The binder can be useful for improving the shape stability and strength of the heat insulating layer. In the embodiment in which the heat insulating layer contains a binder, the type of the binder is not particularly limited, and may be an organic binder or an inorganic binder. Specific examples of organic binders include thermoplastic resins, thermoplastic elastomers, thermosetting resins, thermosetting elastomers, sugars, water-soluble polymers, and the like. Specific examples of inorganic binders include aluminum oxide, zirconium oxide, magnesium oxide, titanium oxide, calcium oxide, and the like. From the viewpoint of heat resistance and flame resistance, inorganic binders are generally more advantageous than organic binders. The heat insulating layer may contain one type of binder, or may contain two or more types of binders. Alternatively, it may be substantially free of binders.
[0038] When the heat insulating layer contains a binder, the content of the binder is not particularly limited and can be appropriately set so as to obtain the desired use effect. In some embodiments, the content of the binder in the heat insulating layer may be, for example, 0.01% by mass to 10% by mass of the heat insulating layer, preferably 0.05% by mass or more, more preferably 0.1% by mass or more, even more preferably 0.2% by mass or more, and preferably 5% by mass or less, more preferably 3% by mass or less, and even more preferably 1% by mass or less. In addition, in an embodiment in which the heat insulating layer contains inorganic fibers, when the content of the binder in the heat insulating layer is within the above range, the heat insulating property and shape stability of the heat insulating layer are easily compatible.
[0039] The heat insulating layer may contain inorganic particles other than silica particles. The type of inorganic particles other than silica particles is not particularly limited. Examples of inorganic particles other than silica include zinc oxide, aluminum oxide, titanium oxide particles, silicon carbide particles, ilmenite particles (ilmenite, FeTiO), zirconium silicate particles, iron (III) oxide particles, iron (II) (wustite (FeO) particles, magnetite particles (Fe3O4), hematite particles (Fe2O3)), chromium dioxide particles, zirconium oxide particles, manganese dioxide particles, zirconia sol, titania sol, silica sol, alumina sol, bentonite particles, kaolin particles, etc. In some embodiments, the above-mentioned description of the average particle size and BET specific surface area of silica particles can be applied to the average particle size (primary average particle size, average particle size of secondary aggregates) and BET specific surface area of inorganic particles other than silica particles.
[0040] Other examples of inorganic particles other than silica particles include carbon-based particles such as graphite, carbon black, and carbon powder. Graphite preferably has a particle size of 18 μm or less. The particle size of graphite is measured in the same manner as the average primary particle size of silica particles. When a nominal value of the particle size is provided by a manufacturer or the like, the nominal value may be adopted. The shape of graphite may be any shape such as flake, scaly, or spherical. Examples of commercially available flake graphite include BF-3AK, FBF, and BF-10AK manufactured by Chuetsu Graphite Industries Co., Ltd., and GE-1, Z-5F, CNP7, and V-10F manufactured by Ito Graphite Industries Co., Ltd. Examples of commercially available scaly graphite include HLP and SB-1 manufactured by Chuetsu Graphite Industries Co., Ltd. Examples of commercially available spherical graphite include SG-BH8 manufactured by Ito Graphite Industries Co., Ltd. Examples of commercially available carbon black include TOKABLACK #5500 manufactured by Tokai Carbon Co., Ltd. and MA100 manufactured by Mitsubishi Chemical Corporation. In some embodiments in which carbon black is used as inorganic particles, the carbon black may preferably have a relatively high DBP oil absorption from the viewpoint of reducing thermal conductivity, although this is not particularly limited. The DBP oil absorption is suitably, for example, 40 mL / 100 g or more, and preferably 60 mL / 100 g or more or 80 mL / 100 g or more.
[0041] The heat insulating material may contain only one type of inorganic particles other than silica particles, or may contain two or more types. In some embodiments, the inorganic particles other than silica particles are preferably inorganic particles that can suppress thermal radiation, more specifically, inorganic particles that have an absorption peak in the infrared region.
[0042] In the heat insulating material disclosed herein, the proportion of silica particles among the inorganic particles contained in the heat insulating layer is preferably 50% by mass or more, more preferably 70% by mass or more, and may be 85% by mass or more, 90% by mass or more, or may be 95% by mass or more. The inorganic particles may be substantially composed of silica particles. Here, "substantially" means that inorganic particles other than silica particles are not contained at least intentionally, and inorganic particles other than silica particles may be unintentionally contained as impurities or crushed materials of other components.
[0043] The heat insulating layer may contain organic fibers. Specific examples of organic fibers include felts made of cellulose fibers, polyesters, polypropylenes, etc. The use of organic fibers can be advantageous in terms of improving cushioning properties and durability against repeated pressure fatigue. It is preferable to use organic fibers in combination with inorganic fibers. The content of organic fibers in the heat insulating layer can be appropriately set so as to obtain a desired use effect, and may be, for example, 0.01% by mass or more, 0.5% by mass or more, or 3% by mass or more of the heat insulating layer, and may be, for example, 20% by mass or less, 10% by mass or less, or 5% by mass or less. In some embodiments, from the viewpoint of heat resistance, flame resistance, etc., the content of organic fibers in the heat insulating layer is preferably less than 3% by mass, more preferably less than 1% by mass, and may be less than 0.1% by mass or less than 0.01% by mass. The heat insulating layer may be substantially free of organic fibers.
[0044] (The shape and characteristics of the heat insulating layer, etc.) The thickness of the heat insulating layer is not particularly limited, and may be, for example, about 0.3 mm to 10 mm, preferably 0.5 mm or more, 0.7 mm or more, 0.8 mm or more, or 0.9 mm or more. From the viewpoint of heat insulating performance and insulation performance, it is advantageous for the heat insulating layer to be thicker. In some embodiments, the thickness of the heat insulating layer may be, for example, 1.0 mm or more, 1.2 mm or more, 1.5 mm or more, or 2.0 mm or more. In some embodiments, the thickness of the heat insulating layer may be, for example, 9.0 mm or less, preferably 7.0 mm or less, more preferably 5.0 mm or less, 3.0 mm or less, 2.0 mm or less, 1.5 mm or less, or 1.3 mm or less. By reducing the thickness of the heat insulating layer, the heat insulating material can be made thinner and lighter. The thickness of the insulating layer can be the average value of the values obtained by measuring the cross section of the insulating layer at several points (e.g., 10 points) with a thickness gauge (e.g., Ozaki Seisakusho's digital thickness gauge JAN-257 (measuring probe Φ20)).
[0045] The density of the heat insulating layer is not particularly limited and is, for example, 0.2 g / cm 3 ~0.5g / cm 3 In some embodiments, the density of the insulating layer is preferably 0.3 g / cm 3 More preferably, 0.35 g / cm 3 More preferably, 0.37 g / cm 3 More preferably, it is 0.45 g / cm 3 The following is the result.
[0046] The shape of the heat insulating layer is not particularly limited. In some embodiments, the shape of the heat insulating layer when viewed from above can be, for example, a polygon such as a quadrangle, a circle, an ellipse, etc. Examples of quadrangles include rectangles (including squares and rectangles).
[0047] The thermal conductivity of the insulating layer at 80°C and 2 MPa pressure is usually 0.3 W / K·m or less, preferably 0.1 W / K·m or less, more preferably 0.08 W / K·m or less, 0.06 W / K·m or less, 0.055 W / K·m or less, 0.045 W / K·m or less, or 0.04 W / K·m or less, and may be, for example, 0.010 W / K·m or more. The thermal conductivity of the insulating layer at 600°C and 2 MPa pressure is usually 0.3 W / K·m or less, preferably 0.2 W / K·m or less, more preferably 0.1 W / K·m or less, 0.08 W / K·m or less, or 0.075 W / K·m or less, and may be, for example, 0.010 W / K·m or more. The thermal conductivity of the insulating layer is preferably lower than that of the buffer layer described below under at least one of the above conditions of 80° C. and 2 MPa pressure or 600° C. and 2 MPa pressure. In some embodiments, the thermal conductivity of the insulating layer can be, for example, 90% or less, 75% or less, or 50% or less of the thermal conductivity of the buffer layer.
[0048] When the thickness (initial thickness) of the insulation layer is adjusted to 2 mm without pressure, the thermal resistance at 80°C and 2 MPa pressure is, for example, 0.020 (K m 2 ) / W or more, preferably 0.025(K m 2 ) / W or more, 0.03(K m 2 ) / W or more or 0.035(K m 2 ) / W or more, and for example, 0.1(K m 2 ) / W or less. The thermal resistance of an insulating layer with an initial thickness of 2 mm at 600°C and a pressure of 2 MPa is, for example, 0.010(K·m 2 ) / W or more, preferably 0.015(K m 2 ) / W or more or 0.020(K m 2 ) / W or more, and for example, 0.1(K m 2 ) / W or less.
[0049] The thermal conductivity of the insulating layer can be measured by the method described in Japanese Industrial Standard JIS A 1412-2:1999 "Methods for measuring thermal resistance and thermal conductivity of thermal insulating materials - Part 2: Heat flow meter method (HFM method)."
[0050] The heat flow meter method (HFM method) is a secondary measurement method or comparative measurement method that measures heat transfer characteristics such as thermal conductivity and thermal resistance by comparing a flat thermal insulation material (insulation layer) as a test specimen with a standard plate. The detailed measurement procedure and measurement conditions are explained below.
[0051] The insulation layer is cut to a specified size (e.g., 20 mm x 20 mm) to prepare the test specimen, and an alumina composite material (RS-100, manufactured by ZIRCAR Refractory Composites, Inc., thickness: 5 mm, thermal conductivity: 0.66 W / K·m) is prepared as the standard plate. Next, the first thermocouple, titanium plate, insulation layer, titanium plate, second thermocouple, standard plate, and third thermocouple are placed on the lower plate of the pneumatic press in this order from the top, and the test specimen, standard plate, thermocouple, etc. are tightly pressed between the upper and lower plates. The upper and lower plates are then heated to the specified measurement temperature, and the test specimen is pressed by the pneumatic press to the specified measurement pressure.
[0052] The measurement temperatures may be, for example, 80° C. for the upper plate on the first thermocouple side and 30° C. for the lower plate on the third thermocouple side. On the other hand, the measurement temperatures under high temperature conditions may be, for example, 600° C. for the upper plate on the first thermocouple side and 40° C. for the lower plate on the third thermocouple side.
[0053] The measurement pressure can be, for example, 2 MPa (load: 800 N). Measurement is continued under heating and pressure until the temperature detected by each thermocouple stabilizes, and the thermal conductivity k1 of the insulating layer can be calculated from the detected temperature of each thermocouple after the temperature has stabilized, the thickness of the insulating layer when pressurized, the thermal conductivity of the standard plate, and the thickness of the standard plate when pressurized, according to the following formula (I). k1=k2×(L1×ΔT1) / (L2×ΔT2) ···(I) (In the formula, k1 is the thermal conductivity of the insulation layer [W / (m K)], k2 is the thermal conductivity of the standard plate [W / (m K)], L1 is the thickness of the insulation layer when pressed, L2 is the thickness of the standard plate, ΔT1 is the temperature difference between the temperatures of the second and third thermocouples, and ΔT2 is the temperature difference between the temperatures of the first and second thermocouples.) Note that the detected temperature being stable means, for example, that the temperature change after about 10 minutes falls within a specified range (for example, within ±0.1°C).
[0054] The thermal resistance of the heat insulating layer can be calculated from the above-mentioned thermal conductivity k1 and thickness under pressure L1 according to the following formula (II). R1 = L1 / k1 (II) (Wherein, R1 is the thermal resistance of the insulation layer [(m 2 K / W], k1 is the thermal conductivity of the insulation layer [W / (m K)], and L1 is the thickness of the insulation layer when pressed.)
[0055] (Creating a heat insulating layer) The method of producing the heat insulating layer disclosed herein is not particularly limited, and can be produced by appropriately adopting known processes. For example, a mixture containing silica particles and other optional components (inorganic fibers, dispersants, etc.) that can be used as needed can be prepared by known mixing methods such as a wet method and a dry method, and the mixture can be used to produce a heat insulating layer. As a method of producing a heat insulating layer that includes preparing the mixture (typically a slurry-like mixed liquid) by a wet method, for example, a method including the following steps can be mentioned. Mixing step: A step of mixing silica particles with other optional components (inorganic fibers, dispersants, etc.) that may be used as necessary in a solvent to obtain a mixed liquid. Coating step: A step of applying the above-mentioned mixed solution to obtain a coating film. Forming process: A process of forming the coating film to obtain a heat insulating layer.
[0056] The mixing in the mixing step can be carried out using, for example, a Disper, a Labo Plastomill, a Trimix, a planetary mixer, a kneader, or the like.
[0057] The type of solvent is not particularly limited. For example, a solvent selected from protic solvents such as alcohols (e.g., alcohols having 1 to 4 carbon atoms, such as methanol, ethanol, isopropyl alcohol, and ethylene glycol), amides, and water, and aprotic solvents such as esters, ketones, nitriles, and ethers, can be used. A mixed solvent containing two or more solvents can also be used.
[0058] The surface tension of the solvent is not particularly limited, and is, for example, 20 mN / m to 73 mN / m, preferably 21 mN / m or more, preferably 50 mN / m or less, more preferably 40 mN / m or less, and further preferably 30 mN / m or less. When the surface tension of the solvent is within the above range, a heat insulating material exhibiting good heat insulating properties and mechanical strength is easily obtained. The above-mentioned range of surface normal force can also be applied to the surface tension of a mixed solvent. The surface tension of a solvent (which may be a mixed solvent) can be measured by the ring method. The surface tension of a mixed solvent obtained by mixing isopropyl alcohol (surface tension: 21 mN / m) and water (surface tension: 73 mN / m), which are protic solvents, in a mass ratio of 5:1 is about 23 mN / m.
[0059] The consistency (initial consistency) of the mixed liquid is not particularly limited, but may be, for example, within the range of about 50 to 200. In some embodiments, the initial consistency of the mixed liquid is, for example, 55 or more, 60 or more, or 65 or more, preferably 70 or more, more preferably 75 or more, even more preferably 80 or more, and particularly preferably 85 or more (for example, 90 or more). For example, in the production of a heat insulating layer containing inorganic fibers, it is preferable that the initial consistency of the mixed liquid is not too low from the viewpoint of reducing fiber breakage of the inorganic fibers during preparation, stirring, feeding, application, etc. of the mixed liquid. In addition, in some embodiments, the initial consistency of the mixed liquid is preferably 180 or less, more preferably 160 or less, and even more preferably 140 or less (for example, 120 or less or 110 or less). It may be advantageous that the initial consistency of the mixed liquid is not too high from the viewpoint of moldability when the mixed liquid is molded to obtain a heat insulating layer, shape accuracy of the molded product (heat insulating layer), etc.
[0060] The method for measuring the consistency of the mixed liquid includes the method described in the Japanese Industrial Standard JIS K 2220:2013 "Grease - Part 7: Consistency Test Method", and in particular, the method of measuring the consistency as "immiscible consistency". Measuring instruments that can measure consistency are commercially available, and specifically, the PENETRO METER manufactured by Nikka Engineering Co., Ltd. can be mentioned. The measurement procedure is to prepare a pot large enough that the conical weight does not come into contact with the weight when it is lowered, fill it with the mixed liquid, and place it on the measuring instrument to which the weight is attached. Next, the position of the weight is adjusted to a position where the weight and the mixed liquid come into contact, and that position is set as the zero point. Then, under room temperature (25°C) conditions, the weight is lowered for 5 seconds (±0.1 seconds), and the depth (mm) of the weight that has penetrated into the mixed liquid x 10 is calculated as the consistency. The conical weight should be a standard cone as specified in the Japanese Industrial Standards, with a total mass of 102.5g±0.05g and a mass of the weight holder of 47.5±0.05g.
[0061] The coating method and conditions in the coating step are not particularly limited, and any known method can be appropriately used. For example, coating can be performed using a comma coater, spin coater, die coater, roll coater, calendar roll, dispenser, etc.
[0062] The molding method and molding conditions in the molding step are not particularly limited, and known methods can be appropriately adopted. For example, compression molding using a heat press or a vacuum press, and drying using a floating oven, an IR oven, etc. are included. The drying temperature is preferably, for example, 60°C to 150°C. The drying time is preferably, for example, 4 minutes to 20 minutes.
[0063] <Buffer layer> The thermal insulation material disclosed herein includes a buffer layer in addition to the above-mentioned thermal insulation layer. The buffer layer can contribute to improving the wind pressure resistance of the thermal insulation material by protecting or supporting the thermal insulation material. The buffer layer can also be useful for adjusting the compressive properties of the thermal insulation material as a whole (e.g., improving compressive deformability).
[0064] As the buffer layer, a fiber molded body mainly composed of inorganic fibers is used. The fiber molded body may contain one type of inorganic fiber or may contain two or more types of inorganic fibers. The aggregate form of the inorganic fibers may be any of nonwoven fabric, woven fabric, knitted fabric, etc., and may be, for example, a nonwoven fabric. The type of inorganic fiber is not particularly limited, and examples thereof include alkaline earth silicate (AES) fiber, silica-alumina fiber, alumina fiber, zirconia fiber, silica fiber, glass fiber, rock wool, basalt fiber, glass wool, etc. Examples of inorganic fibers that are preferable from the viewpoint of flame resistance include AES fiber, silica-alumina fiber, and alumina fiber. For example, a buffer layer containing one or more types of inorganic fibers selected from the group consisting of AES fiber, silica-alumina fiber, and alumina fiber is preferable. In such a buffer layer, the combined amount of the AES fibers, silica-alumina fibers, and alumina fibers in the total mass of the inorganic fibers contained in the buffer layer is preferably 50 mass% or more, more preferably 70 mass% or more, and may be 85 mass% or more, 90 mass% or more, or 95 mass% or more, or may be 100 mass%.
[0065] The AES fiber may have a chemical composition containing alkaline earth metal oxides (MgO and / or CaO) and silica (SiO2), with the silica content being approximately 40% by mass or more (e.g., 45% by mass or more or 50% by mass or more) and 90% by mass or less (e.g., 85% by mass or less or 82% by mass or less), and the total content of alkaline earth metal oxides being approximately 10% by mass or more (e.g., 12% by mass or more or 15% by mass) and 50% by mass or less (e.g., 45% by mass or less or 43% by mass or less). In some embodiments, from the viewpoint of heat resistance and the like, the silica content in the AES fiber is preferably 60% by mass or more, more preferably 65% by mass or more, and even more preferably 70% by mass or 75% by mass or more. In order to relatively increase the silica content, in some embodiments, the total content of alkaline earth metal oxides in the AES fiber is suitably 35% by mass or less, and preferably 30% by mass or less or 25% by mass or less. The AES fiber may contain metal oxides other than alkaline earth metal oxides, such as Al2O3, TiO2, ZrO2, etc., as optional components other than alkaline earth metal oxides and silica. The total content of Al2O3, TiO2, and ZrO2 in the AES fiber is suitably less than 15% by mass, and preferably less than 10% by mass (e.g., 6% by mass or less or 4% by mass or less). In some embodiments, the total content of alkaline earth metal oxides and silica in the AES fiber is suitably 80% by mass or more, and preferably 85% by mass or more (e.g., 90% by mass or more).
[0066] The silica-alumina fiber may have a chemical composition that includes silica and alumina (Al2O3), and the silica content is generally 35% by mass or more (e.g., 40% by mass or more or 45% by mass or more) and 70% by mass or less (e.g., 65% by mass or less, 60% by mass or less, or 55% by mass or less), and the alumina content is generally 25% by mass or more (e.g., 30% by mass or more or 35% by mass or more) and 65% by mass or less (e.g., 60% by mass or less or 55% by mass or less). The silica-alumina fiber may contain a transition metal oxide such as ZrO2 or Cr2O3 as an optional component other than silica and alumina. The content of the transition metal oxide may be, for example, 15% by mass or less, 10% by mass or less, 5% by mass or less, or 1% by mass or less. In some embodiments, the total content of silica and alumina in the silica-alumina fibers is suitably 60% by weight or more, preferably 70% by weight or more, more preferably 80% by weight or more, may be 85% by weight or more, 90% by weight or more, or 95% by weight or more, or may be 100% by weight.
[0067] The alumina fiber may have a chemical composition in which alumina is the main component and silica is included, the alumina content is more than 65 mass% (e.g., 70 mass% or more, 75 mass% or more, or 80 mass% or more) and 99 mass% or less (e.g., 97 mass% or less or 95 mass% or less), and the silica content is 1 mass% or more (e.g., 3 mass% or more or 5 mass% or more) and less than 35 mass% (e.g., 30 mass% or less, 25 mass% or less, or 20 mass% or less). In some embodiments, the total content of silica and alumina in the alumina fiber is suitably 70 mass% or more, preferably 80 mass% or more, more preferably 90 mass% or more, and may be 95 mass% or more, 98 mass% or more, or may be 100 mass%.
[0068] The content of inorganic fibers in the buffer layer is, for example, 50% by mass or more, preferably 60% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more (for example, 82% by mass or more), and may be 85% by mass or more or 90% by mass or more. The content of inorganic fibers in the fiber molded product may be 100% by mass, or may be 99% by mass or less, or may be 97% by mass or less, 95% by mass or less, or 93% by mass or less. A buffer layer containing inorganic fibers in any of the above-mentioned amounts easily achieves a good balance between heat resistance and strength, and also makes it easy to adjust the compression characteristics of a heat insulating material containing the buffer layer to a preferred range.
[0069] The average fiber length of the inorganic fibers contained in the buffer layer is not particularly limited and may be, for example, within the range of 0.1 mm to 200 mm. In some embodiments, the average fiber length of the inorganic fibers is preferably 1 mm or more (for example, 5 mm or more), more preferably 10 mm or more, and even more preferably 20 mm or more, and is preferably 175 mm or less, more preferably 150 mm or less, and even more preferably 125 mm or less, and may be 100 mm or less, 75 mm or less, or 50 mm or less. When the average fiber length of the inorganic fibers is within the above range, it is easy to exhibit appropriate buffering properties.
[0070] The average fiber diameter of the inorganic fibers contained in the buffer layer is not particularly limited, and may be, for example, within the range of 1 μm to 15 μm. In some embodiments, the average fiber diameter of the inorganic fibers is typically 2 μm or more, for example, 2.5 μm or more, and may be 3 μm or more, or may be 4 μm or more. In some embodiments, the average fiber diameter of the inorganic fibers is typically 10 μm or less, for example, 9 μm or less, and may be 8 μm or less, 7 μm or less, 6 μm or less, or 5 μm or less. When the average fiber diameter of the inorganic fibers is within the above range, it is easy to achieve both moderate cushioning properties and low thermal conductivity.
[0071] The buffer layer may contain a binder (binding agent) in addition to inorganic fibers. The binder may be useful for improving the shape stability and strength of the buffer layer. In an embodiment in which the buffer layer contains a binder, the type of the binder is not particularly limited, and may be an organic binder or an inorganic binder. Specific examples of organic binders include thermoplastic resins, thermoplastic elastomers, thermosetting resins, thermosetting elastomers, sugars, water-soluble polymers, and the like. Specific examples of inorganic binders include aluminum oxide, zirconium oxide, magnesium oxide, titanium oxide, calcium oxide, and the like. From the viewpoint of heat resistance and flame resistance, inorganic binders are generally more advantageous than organic binders. The buffer layer may contain one type of binder, or may contain two or more types of binders. Alternatively, it may be substantially free of binders.
[0072] The content of the binder in the case where the heat insulating layer contains a binder is not particularly limited and can be appropriately set so as to obtain the desired effect of use. In some embodiments, the content of the binder in the buffer layer may be, for example, 0.01% by mass or more of the buffer layer, 0.1% by mass or more, 1% by mass or more, 2% by mass or more, 5% by mass or more, 7% by mass or more, 10% by mass or more, or 12% by mass or more. In addition, the content of the binder in the buffer layer is usually appropriate to be 40% by mass or less of the buffer layer, advantageously 30% by mass or less, preferably 25% by mass or less, more preferably 20% by mass or less, may be 18% by mass or less or 16% by mass or less, may be 13% by mass or less, 10% by mass or less, 7% by mass or less, 5% by mass or less, or 3% by mass or less. When the content of the binder is within the above range, it is easy to achieve a good balance between low thermal conductivity and buffering properties in the buffer layer.
[0073] In some embodiments, the fiber molded body as the buffer layer preferably contains inorganic fibers and does not contain hydrophilic fumed silica. The fiber molded body may be, for example, a molded body containing inorganic fibers and not containing silica particles, or a molded body containing inorganic fibers and not containing inorganic particles. The inorganic fibers used to prepare the fiber molded body may be sold as a sheet in an aggregate form such as a nonwoven fabric, woven fabric, knitted fabric, etc., in a state in which a thermosetting resin as a binder is dispersed (attached to at least a part of the inorganic fibers). The inorganic fibers in such a form may be cut to a desired size, and then heated and compressed to form a fiber molded body.
[0074] (Shape, characteristics, etc. of the buffer layer) The thickness of the buffer layer is not particularly limited, and may be selected, for example, from the range of about 0.2 mm to 10 mm. In some embodiments, the thickness of the buffer layer is suitably 0.3 mm or more from the viewpoint of buffering properties and strength, preferably 0.5 mm or more, may be 0.8 mm or more, may be 1 mm or more, may be 1.5 mm or more, or may be 2 mm or more. In some embodiments, the thickness of the buffer layer is suitably 8 mm or less from the viewpoint of thinning the insulating material, and is advantageously 7 mm or less or 6 mm or less, and may be 5 mm or less or 4 mm or less, and may be 3 mm or less, 2.5 mm or less, 2 mm or less, 1.5 mm or less, or 1.2 mm or less. When the thickness of the buffer layer is within the above range, the insulating material including the buffer layer is likely to obtain a buffering property capable of appropriately buffering the stress generated by the expansion of the battery (for example, the expansion caused by the charging of the cell). The thickness of the buffer layer is measured in the same manner as the insulating layer by measuring the cross-sectional thickness of the buffer layer using a thickness gauge (digital thickness gauge JAN-257, gauge head Φ20, manufactured by Ozaki Seisakusho), and the average value of the values obtained by performing this measurement at any 10 points can be used.
[0075] The shape of the buffer layer is not particularly limited. In some embodiments, the shape of the buffer layer when viewed in plan can be, for example, a polygon such as a quadrangle, a circle, an ellipse, etc. Examples of quadrangles include rectangles (including squares and rectangles).
[0076] (Thermal properties of the buffer layer) The thermal conductivity of the buffer layer is not particularly limited. In some embodiments, the thermal conductivity of the buffer layer under conditions of 80° C. and 2 MPa may be, for example, 1.0 W / K·m or less, usually 0.5 W / K·m or less, preferably 0.2 W / K·m or less, 0.15 W / K·m or less, or 0.1 W / K·m or less, or may be, for example, 0.02 W / K·m or more, 0.030 W / K·m or more, 0.040 W / K·m or more, or 0.050 W / K·m or more. The thermal conductivity of the buffer layer under conditions of 600°C and 2 MPa may be, for example, 1.5 W / K·m or less, usually 1.0 W / K·m or less, and preferably 0.30 W / K·m or less, or 0.25 W / K·m or less, or 0.20 W / K·m or less, and may be, for example, 0.04 W / K·m or more, 0.05 W / K·m or more, or 0.06 W / K·m or more. The thermal conductivity of the buffer layer can be measured by a method similar to that for measuring the thermal conductivity of the insulating layer.
[0077] The thermal resistance of the buffer layer is not particularly limited. In some embodiments, the thermal resistance of the buffer layer under conditions of 80° C. and 2 MPa is preferably 0.020 (K·m 2 ) / W or more, preferably 0.025(K·m 2 ) / W or more, and more preferably 0.03(K m 2 ) / W or more, and preferably 0.07(K·m 2 ) / W or less, more preferably 0.06(K·m 2 ) / W or less, and more preferably 0.05(K·m 2 ) / W or less. The thermal resistance of the insulating layer at 600°C and 2 MPa is preferably 0.001 (K·m 2) / W or more, preferably 0.003(K·m 2 ) / W or more, and more preferably 0.005(K m 2 ) / W or more, and preferably 0.1 (K m 2 ) / W or less, more preferably 0.05(K·m 2 ) / W or less, and more preferably 0.01(K m 2 ) / W or less. The thermal resistance of the buffer layer can be measured by the same method as that for measuring the thermal resistance of the heat insulating layer.
[0078] <Thermal insulation> The heat insulating material disclosed herein is in the form of a sheet having a first surface and a second surface, and includes any of the heat insulating layers described above and any of the buffer layers described above. Each of the first surface and the second surface is composed of any of the heat insulating layers and the buffer layers. The heat insulating material preferably has flame resistance that is evaluated as passing in the following burner test, regardless of whether the first surface or the second surface is the surface to be evaluated. More specifically, the burner test is performed by a method described in the examples below. An insulation material having such flame resistance can have a performance (burst resistance) that can properly maintain its heat insulating function even if local wind pressure or high heat is applied due to the burst of adjacent cells. In addition, since both the first surface and the second surface of the heat insulating material have the above-mentioned flame resistance, it can deal with the burst of adjacent cells on either the first surface side or the second surface side. [Burner test] The surface to be evaluated of the insulation material is heated to 750°C for 2 minutes using a burner, and if no through holes are formed in the layer that constitutes the surface to be evaluated, it is rated as "passed."
[0079] The heat insulating material disclosed herein is capable of performing the burner test at a heating temperature T higher than 750° C. BWhen the heating temperature T is set at [°C], it is preferable that no through holes are generated in the layer constituting the surface to be evaluated in the burner test in which at least one of the first surface and the second surface is the surface to be evaluated, and it is more preferable that no through holes are generated in the layer constituting the surface to be evaluated in which either the first surface or the second surface is the surface to be evaluated. B [° C.] is preferably 800° C., more preferably 1000° C., and further preferably 1200° C. An insulating material having such flame resistance can exhibit better burst resistance.
[0080] In some embodiments of the insulation material disclosed herein, the insulation material is heated to the heating temperature T B In addition to flame resistance that is evaluated as pass (i.e., no through holes are formed) for either the first surface or the second surface in a burner test with a temperature [°C] of 750°C (more preferably 800°C, even more preferably 1000°C, and particularly preferably 1200°C), it is preferable that the insulation material has wind pressure resistance that is evaluated as pass in the following air blow test for either the first surface or the second surface. More specifically, the following air blow test is performed by a method described in, for example, the Examples below. An insulation material having such flame resistance and wind pressure resistance can exhibit better burst resistance. [Air blow test] Air at a flow rate of 940 L / min is sprayed from a nozzle with a diameter of 6 mm for 60 seconds from a position 10 mm in the normal direction of the surface of the insulation being evaluated, and if no through holes are formed in the layer that makes up the surface being evaluated, it is rated as "passed."
[0081] The number of the insulation layers and the number of the buffer layers included in the insulation material disclosed herein may be 1 or 2 or more. When the number of the insulation layers included in the insulation material is 2 or more, the above description of the insulation layers may be applied independently to each insulation layer included in the insulation material. The two or more insulation layers may be the same insulation layer or may be insulation layers that are different from each other (e.g., at least one of composition, density, and thickness is different). Similarly, when the number of the buffer layers included in the insulation material is 2 or more, the above description of the buffer layers may be applied independently to each buffer layer included in the insulation material. The two or more buffer layers may be the same buffer layer or may be buffer layers that are different from each other (e.g., at least one of composition, density, and thickness is different).
[0082] In some embodiments, the number of insulating layers contained in the insulation material is suitably 5 or less, and from the viewpoint of facilitating both thinning of the insulation material and durability of the insulation layers (e.g. wind pressure resistance), it is preferably 3 or less, and more preferably 2 or less. In some preferred embodiments, the number of insulating layers contained in the insulation material may be 1. Also, in some embodiments, the number of buffer layers contained in the insulation material is suitably 5 or less, and from the viewpoint of facilitating both thinning of the insulation material and cushioning properties, it is preferably 3 or less, and more preferably 2 or less. In some preferred embodiments, the number of buffer layers contained in the insulation material may be 1.
[0083] The total number of the insulating layers and the buffer layers contained in the insulating material (total number of layers of the insulating material) may be, for example, 10 or less, and from the viewpoint of facilitating thinning of the insulating material, it is usually appropriate that it is 7 or less or 6 or less, and preferably 5 or less, 4 or less, or 3 or less. Not having too many total layers of the insulating material can be advantageous from the viewpoint of achieving a good balance between thinning of the insulating material and durability (e.g. wind pressure resistance) of the layers exposed on the surface of the insulating material. The technology disclosed herein can be preferably implemented in an embodiment in which the total number of layers of the insulating material is 2, that is, an embodiment in which the insulating material includes only one insulating layer and one buffer layer.
[0084] In some embodiments of the technology disclosed herein, it is preferable that either one of the first surface and the second surface of the heat insulating material is constituted by the heat insulating layer, and the other surface is constituted by the buffer layer. The heat insulating material may have, for example, a heat insulating material / buffer material configuration, a first heat insulating material / second heat insulating material / buffer material configuration, a heat insulating material / first buffer material / second buffer material configuration, a heat insulating material / buffer material / heat insulating material / buffer material configuration, etc. When implemented in a minimum configuration, for example, a heat insulating material having such a configuration can have only one heat insulating layer and one buffer layer, and is therefore suitable for making the heat insulating material thinner.
[0085] The heat insulating layer and the buffer layer included in the heat insulating material may be bonded to the adjacent layers by an adhesive or a pressure sensitive adhesive, or may not be bonded by an adhesive or a pressure sensitive adhesive. In some embodiments, it is preferable that they are not bonded by an adhesive or a pressure sensitive adhesive. By not bonding by an adhesive or a pressure sensitive adhesive, that is, by not using an adhesive or a pressure sensitive adhesive, it is possible to suppress the increase in thermal conductivity compared to when an adhesive or a pressure sensitive adhesive is used. The heat insulating material disclosed herein can be preferably implemented in an embodiment in which the heat insulating layer and the buffer layer are laminated in direct contact with each other. Here, the heat insulating layer and the buffer layer are laminated in direct contact with each other means that there is no continuous layer (e.g., a resin film, a metal foil, etc.) that does not fall under any of the above between the heat insulating layer and the buffer layer.
[0086] The thickness (total thickness) of the heat insulating material disclosed herein is not particularly limited, and may be selected, for example, from the range of about 0.5 mm to 20 mm. In some embodiments, the thickness of the heat insulating material is, from the viewpoint of easily achieving a good balance between heat insulating property and cushioning property, suitably 0.8 mm or more, preferably 1.0 mm or more, may be 1.2 mm or more, may be 1.5 mm or more, may be 2.0 mm or more, or may be 2.2 mm or more. In some embodiments, the thickness of the heat insulating material is, from the viewpoint of making the heat insulating material thinner, suitably 15 mm or less, advantageously 10 mm or less, preferably 5 mm or less, more preferably 4 mm or less, further preferably 3 mm or less, may be 2.5 mm or less, or may be 2 mm or less.
[0087] The compressive properties of the heat insulating material are not particularly limited and may be appropriately selected depending on the application and the mode of use. In some embodiments, the compressive deformation rate of the heat insulating material at a compressive stress of 0.4 MPa (hereinafter also referred to as "0.4 MPa compressive deformation rate") is suitably within the range of, for example, 10% to 60%. The 0.4 MPa compressive deformation rate of the heat insulating material is measured as the compressive strain [%] when the compressive stress becomes 0.4 MPa in a compression test in which the heat insulating material is compressed in the thickness direction, and more specifically, is measured by the method described in the Examples below. When the 0.4 MPa compressive deformation rate of the heat insulating material is within an appropriate range, for example, in the heat insulating material disposed between the cells of a lithium ion battery module, the expansion of the cells (for example, expansion due to charging) can be appropriately buffered. From the viewpoint of exhibiting better buffering properties, in some embodiments, the 0.4 MPa compressive deformation rate of the heat insulating material is preferably 15% or more, more preferably 20% or more, and may be 25% or more, or may be 30% or more. In addition, from the viewpoint of facilitating the thinning of the insulating material, in some embodiments, the above-mentioned 0.4 MPa compressive deformation rate may be, for example, 55% or less, 50% or less, 45% or less, or 40% or less.
[0088] In some embodiments, the compressive deformation rate of the heat insulating material at a compressive stress of 0.1 MPa (hereinafter also referred to as "0.1 MPa compressive deformation rate") may be within a range of, for example, 5% to 50%. The 0.1 MPa compressive deformation rate of the heat insulating material is measured as the compressive strain [%] when the compressive stress becomes 0.1 MPa in a compression test similar to the above 0.4 MPa compressive deformation rate. When the 0.1 MPa compressive deformation rate of the heat insulating material is in an appropriate range, for example, in an embodiment in which the heat insulating material is used as a heat insulating material disposed between cells of a lithium ion battery module, an appropriate compressive stress can be applied to the cell. In some embodiments, the 0.1 MPa compressive deformation rate of the heat insulating material is preferably 7% or more, more preferably 10% or more, may be 12% or more, or may be 15% or more. In addition, from the viewpoint of facilitating the appropriate performance of the function of cushioning the expansion of the cell, in some embodiments, the 0.1 MPa compressive deformation rate is appropriately 45% or less, preferably 40% or less, may be 35% or less, or may be 30% or less.
[0089] <Coating material> The heat insulating material disclosed herein can be used, for example, in a form in which the heat insulating material is covered with a coating material, i.e., in the form of a heat insulating material with a coating material. Covering the heat insulating material with a coating material is preferable from the viewpoint of suppressing the falling off of the constituent materials of the heat insulating material (for example, silica particles contained in the heat insulating layer) and preventing the scattering of the fallen constituent materials. In addition, by making it into a form of a heat insulating material with a coating material, the handling property and protective property of the heat insulating material can be improved. From the viewpoint of avoiding a significant loss of the compression properties of the heat insulating material, for example, a coating material formed using a resin film can be preferably adopted.
[0090] The type of resin constituting the resin film used as the covering material is not particularly limited. Specific examples of the resin include polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyimide (PI), flame-retardant polycarbonate (PC), breathable porous polyethylene (PE), flame-retardant polyethylene (PE), biaxially oriented nylon film (Ny), etc. As the breathable porous PE, one having a molecular weight of 1 million to 7 million is preferable.
[0091] The thickness of the covering material is not particularly limited, and is, for example, 0.001 mm to 0.2 mm, preferably 0.005 mm or more, more preferably 0.007 mm or more, even more preferably 0.010 mm or more, and preferably 0.15 mm or less, more preferably 0.10 mm or less, and even more preferably 0.050 mm or less. When the thickness of the covering material is within the above range, it is easy to suppress the influence on the compression characteristics of the heat insulating material and to maintain the mechanical strength. The thickness of the covering material can be measured in the same manner as the thickness of the heat insulating layer.
[0092] The total number of layers (sheets) of the covering material covering the heat insulating material is usually 1 or more, preferably 2 or more, and usually 5 or less, preferably 4 or less, and more preferably 3 or less. The above-mentioned 2 or more covering materials may be 2 or more resin films, or one resin film may be folded back to form a 2-layer covering material. When folded back in this way, the total number of layers of the covering material is considered to be 2 layers.
[0093] When the heat insulating material includes two or more layers of covering material, the two or more layers of covering material may sandwich and enclose the heat insulating layer from the thickness direction, and the gap between the covering materials (the space partitioned by the two or more layers of covering material) may be sealed. The method for sealing the gap between the covering materials is not particularly limited, and examples thereof include a method in which a seal part is provided on the outer edge of the covering material and the seal parts between the opposing covering materials are bonded together. The method for bonding the seal parts is not particularly limited, and examples thereof include welding using heat welding, ultrasonic welding, etc., and adhesion using adhesives, pressure sensitive adhesives, etc. In addition, welding may be performed by directly welding the resin of the covering material, or by providing a separate resin layer for welding and welding.
[0094] The covering material that covers the insulating material may or may not be bonded to the outer surface (typically the first surface and / or the second surface) of the insulating material with an adhesive or pressure-sensitive adhesive. In some embodiments, it is preferable that the covering material is not bonded to the outer surface (typically the first surface and / or the second surface) of the insulating material with an adhesive or pressure-sensitive adhesive.
[0095] In the heat insulating material disclosed herein, the heat insulating layer may be covered by two or more covering materials in a breathable manner, and may be sealed in a space partitioned by the covering materials. In some embodiments, the covering material preferably covers (e.g., encapsulates) the heat insulating layer in a breathable manner. The method for realizing the breathable covering is not particularly limited. For example, a covering material having a through hole as a vent, a non-sealed part functioning as a vent at a part of the joint between two or more covering materials, etc. can be used alone or in appropriate combination. The vent is typically provided so as to communicate the inside (insulating material side) of the covering material with the external space. The heat insulating material having a configuration in which the heat insulating material is covered by the covering layer in a breathable manner has good deformability due to the breathability of the covering layer, and is easy to compressively deform due to, for example, the volume expansion of the cells.
[0096] The number of ventilation holes in the covering material is usually 1 or more, preferably 2 or more, and usually 50 or less, preferably 25 or less, and more preferably 10 or less.
[0097] The total open area of the cladding vents is typically 0.000079 cm 2 ~10cm 2 It is preferable that the distance is 0.0001 cm. 2 More than 0.005cm, more preferably 0.005cm 2 More preferably, 0.01 cm 2 More than 5 cm, preferably 2 Less than 4cm, more preferably 2 Less than 3cm, more preferably 2 When the total opening area of the ventilation holes of the covering material is within the above range, even if a part of the constituent material of the insulating material falls off, the fallen matter (e.g., silica particles) is easily prevented from flowing out of the covering material.
[0098] The ventilation hole of the covering layer may be covered with a ventilation membrane. The ventilation membrane usually has a ventilation rate of 4 cm 3 / (cm 2 s)~500cm 3 / (cm 2s), preferably 7 cm 3 / (cm 2 s) or more, preferably 10 cm 3 / (cm 2 s) or more, preferably 21 cm 3 / (cm 2 s) or more, preferably 250 cm 3 / (cm 2 s) or less, preferably 200 cm 3 / (cm 2 s) or less, more preferably 100 cm 3 / (cm 2 ·s) or less.
[0099] <Application> The use of the heat insulating material according to the embodiment of the present invention is not particularly limited, and can be appropriately used in known applications in which heat insulating materials are used. For example, by taking advantage of the feature that it can exhibit good burst resistance, it is preferably used as a heat insulating material arranged between cells of a battery module, etc., and more specifically, it is particularly preferably used as a heat insulating material arranged between cells of a lithium ion battery module, etc. The form of the cell is not particularly limited, and may be, for example, a laminate cell or a rectangular cell. The heat insulating material disclosed herein can be preferably used as a heat insulating material arranged between laminate cells of a battery module, etc.
[0100] Target devices for the batteries include electric vehicles (EVs), hybrid vehicles (HVs), plug-in hybrid vehicles (PHVs), portable electronic devices such as mobile terminals, mobile phones and notebook computers, and wearable devices.
[0101] Fig. 1 is a perspective view showing a schematic diagram of an example of a battery module in which a heat insulating material according to an embodiment is arranged between cells, and Fig. 2 is a cross-sectional view taken along line II-II of Fig. 1. As shown in Fig. 1, a battery module 50 includes a plurality of battery cells (here, rectangular cells) 51 arranged in the thickness direction, and a heat insulating material 1 is arranged between each of the battery cells 51. The plurality of battery cells 51 thus arranged with the heat insulating material 1 sandwiched between them are usually restrained with a pressing force (compressive force) applied in the thickness direction via restraining plates 52a, 52a arranged at both ends, and are housed in a battery case 53 for use.
[0102] As shown in Fig. 2, the insulating material 1 has a structure in which an insulating layer 10 and a buffer layer 20 are laminated. These are sandwiched and wrapped in two resin films (two coating layers) 31A, 31B in the thickness direction to form a coating-attached insulating material 40. The resin films 31A, 31B are sealed by adhesion (for example, thermal welding) at seal portions provided along their outer edges, and are integrated to form the coating material 30. The insulating material 1 having such a structure (the insulating material 1 constituting the coating-attached insulating material 40 in this embodiment) is sandwiched between two adjacent battery cells 51, 51, thereby exerting an effect of insulating the space between the opposing surfaces 51a, 51a of the two battery cells 51, 51.
[0103] FIG. 3 is an enlarged cross-sectional view of the heat insulating material shown in FIG. 2. The heat insulating material 1 has a structure in which the heat insulating layer 10 is laminated on one surface 20a of the buffer layer 20, and the heat insulating material 1 is sandwiched and wrapped in two resin films (two coating layers) 31A, 31B from the thickness direction to form a heat insulating material 40 with coating material. The resin films 31A, 31B are sealed by adhesion (for example, thermal welding) at a seal portion 32 provided along their outer edges, and integrally form the coating material 30. The resin film 31A is formed in a convex shape that generally covers the end face of the laminate of the heat insulating layer 10 and the buffer layer 20, and a vent (through hole) 33 is formed in the part covering this end face. An air permeable membrane 34 is arranged at the opening to the outside of the vent 33 to prevent powder from flowing out from the heat insulating layer.
[0104] As is apparent from the above description and the following examples, the subject matter disclosed in this specification includes the following. [1] A thermal insulation material including a thermal insulation layer and a buffer layer, The thermal insulation layer contains silica particles, The buffer layer is a fiber molded body mainly composed of inorganic fibers, the heat insulating material is in the form of a sheet having a first surface and a second surface, each of the first surface and the second surface being constituted by the heat insulating layer or the buffer layer; The above-mentioned insulating material has flame resistance that is evaluated as passing in the following burner test, regardless of whether the first surface or the second surface is the surface to be evaluated. [Burner test] The surface to be evaluated of the insulation material is heated to 750°C for 2 minutes using a burner, and if no through holes are formed in the layer that constitutes the surface to be evaluated, it is rated as "passed." [2] The insulating material according to [1], wherein one of the first surface and the second surface is constituted by the insulating layer, and the other surface is constituted by the buffer layer. [3] The insulating layer according to [1] or [2] above, wherein the insulating material has wind pressure resistance that is evaluated as passing in the following air blow test, regardless of whether the first surface or the second surface is the surface to be evaluated. [Air blow test] Air at a flow rate of 940 L / min is sprayed from a nozzle with a diameter of 6 mm for 60 seconds from a position 10 mm in the normal direction of the surface of the insulation being evaluated, and if no through holes are formed in the layer that makes up the surface being evaluated, it is rated as "passed." [4] The heat insulating material according to any one of [1] to [3] above, wherein the heat insulating layer contains fumed silica as the silica particles. [5] The heat insulating material according to any one of [1] to [4] above, wherein in the buffer layer, the inorganic fibers contain, as a main component, one or more fibers selected from the group consisting of alkaline earth silicate fibers, silica-alumina ceramic fibers, and alumina fibers. [6] The heat insulating material according to any one of [1] to [5] above, wherein the initial thickness of the heat insulating material is 5 mm or less. [7] The heat insulating material according to any one of the above [1] to [6], wherein the heat insulating material has a compressive deformation rate of 10% or more at a compressive stress of 0.4 MPa. [8] The heat insulating material according to any one of the above [1] to [7], which is covered with a covering material composed of a resin film. [9] The heat insulating material according to any one of [1] to [8] above, which is used by being disposed between adjacent cells among a plurality of cells in a battery module or battery pack including a plurality of arranged cells. EXAMPLES
[0105] <Creating a heat insulating layer> (Thermal insulation layer A) A mixture of 300 parts by mass of isopropyl alcohol (IPA, surface tension: 21 mN / m) as a protic solvent and 60 parts by mass of water (surface tension: 73 mN / m) (surface tension: 23 mN / m) was added to hydrophilic fumed silica (AEROSIL (registered trademark) 200, manufactured by Nippon Aerosil Co., Ltd., average primary particle size: approximately 12 nm, BET specific surface area: 200 m 2 The mixture was mixed with 100 parts by mass of glass fiber ("CS 6J-888", manufactured by Nitto Boseki Co., Ltd., average fiber diameter: 11 μm, average fiber length: 6 mm) which is an inorganic fiber, and Kao Corporation's Coatamin 24P (active ingredient: dodecyltrimethylammonium chloride (C 12 H 25 N + 1.9 parts by mass (0.5 parts by mass as active ingredient) of (CH3)3Cl)), active ingredient content: 27% by mass), was added and mixed to a consistency of 70 to 140. Next, the obtained mixture was applied to a substrate to a thickness of 2.0 mm to form a coating film. Furthermore, the coating film was compression molded with a hot press machine to a sheet shape with a thickness of 1.0 mm, and then dried at 100°C for 10 minutes to produce a heat insulating layer A, which is a molded body (composite material) formed from a mixture containing hydrophilic fumed silica, glass fiber, and a non-polymeric dispersant. The obtained heat insulating layer A had a thickness of 1.0 mm and a density of 0.37 g / cm.3 It was.
[0106] (Thermal insulation layer B) A 1.6 mm thick insulating layer B was prepared in the same manner as insulating layer A, except that the thickness of the coating film formed from the above mixed liquid was changed to 3.2 mm and the thickness of the coating film compressed and molded in a hot press was changed to 1.6 mm.
[0107] (Thermal insulation layer C) A 2.0 mm thick insulating layer C was prepared in the same manner as insulating layer A, except that the thickness of the coating film formed from the above mixed liquid was changed to 4.0 mm and the thickness of the coating film compressed and molded using a hot press was changed to 2.0 mm.
[0108] (Thermal insulation layer D) As the heat insulating layer D, a commercially available silica aerogel sheet (thickness: 2.5 mm) was used.
[0109] <Making of insulation material> (Example 1) A laminate was prepared of the insulating layer A and a 0.5 mm thick alkaline earth silicate (AES) wool sheet as a buffer layer (product name "BSSR Paper", manufactured by Isolite Kogyo, chemical composition: SiO2 77%, CaO+MgO 20%, hereinafter also referred to as "buffer layer A") to form the insulating material of this example.
[0110] (Example 2) A laminate of the heat insulating layer B and the buffer layer A was prepared as the heat insulating material of this example.
[0111] (Example 3) A laminate of the heat insulating layer C and the buffer layer A was prepared as the heat insulating material of this example.
[0112] (Example 4) A laminate of the insulating layer A and a 1.0 mm thick alkaline earth silicate (AES) wool sheet (product name "BSSR Paper", manufactured by Isolite Industries, hereinafter also referred to as "buffer layer B") was prepared as the insulating material of this example.
[0113] (Example 5) A laminate of the insulating layer A and a 4.0 mm thick alkaline earth silicate (AES) wool sheet (product name "BSSR Paper", manufactured by Isolite Industries, hereinafter also referred to as "buffer layer C") was prepared as the insulating material of this example.
[0114] (Example 6) As the heat insulating material according to this example, the heat insulating layer A was used as it was (as a single layer).
[0115] (Example 7) As the heat insulating material according to this example, the heat insulating layer D was used as it was (as a single layer).
[0116] (Example 8) Glass wool (GW) (Uncured wool (500g / m 2 ), manufactured by Central Glass Fiber Co., Ltd., glass wool content: 80-90 mass%, phenol binder content: 10-20 mass%), was heat-cured using a heat press at 240°C and compression-molded to a thickness of 2.0 mm to produce a laminate of the buffer layer D and the insulating layer A, which was used as the insulating material of this example.
[0117] (Example 9) Glass wool (GW) (Uncured wool (500g / m 2 ), manufactured by Central Glass Fiber Co., Ltd., glass wool content: 80-90 mass%, phenol binder content: 10-20 mass%), was heat-cured using a hot press at 240°C and compression-molded to a thickness of 5.0 mm to produce a laminate of the buffer layer E and the insulating layer A, which was used as the insulating material of this example.
[0118] (Example 10) A laminate was prepared of the insulating layer A and a 5.0 mm thick ethylene-propylene-diene rubber (EPDM) foam sheet (EPTSealer (registered trademark) EE-1000, thickness 5.0 mm, manufactured by Nitto Denko Corporation, hereinafter also referred to as "buffer layer F"), and this was used as the insulating material for this example.
[0119] <Measurement and Evaluation> (Compression deformation rate) For the thermal insulating materials according to Examples 1 to 9, the compressive deformation ratio was measured by the following method. A compression test was conducted by compressing the insulation material at a compression speed of 0.5 mm / min using a precision universal testing machine (Autograph AGS-5kNX, manufactured by Shimadzu Corporation), and the compressive strain [%] (compressive displacement amount / initial thickness of the test piece) and compressive stress [MPa] were measured. The compressive strain [%] was read when the compressive stress reached 0.4 MPa, and this was used as the compressive deformation rate [%] of the insulation material. The results are shown in Table 1.
[0120] (Burner test) For the insulation materials according to each example, a burner test was performed using the device shown in FIG. 4, with the first and second surfaces of the insulation material as the evaluation target surfaces. Specifically, a thermocouple 61 was attached to the evaluation target surface side of the insulation material 1, and the insulation material was sandwiched between two stainless steel plates 62, 62 having a circular opening 62a with a diameter of 5 mm in the center. This was held in a position in which the surface direction of the insulation material 1 was almost vertical, and the insulation material 1 exposed from the opening 62a was heated at 750°C for 2 minutes using a burner 63. A gas cylinder "Power Gas Pro Regular RZ-850" manufactured by Shinfuji Burner Co., Ltd. was used to supply fuel to the burner 63. After cooling, the insulation material 1 was visually observed, and if no through holes were generated in the layer constituting the evaluation target surface, the flame resistance was evaluated as "○" (pass), and if a through hole was generated, the flame resistance was evaluated as "×" (fail). The results are shown in Table 1.
[0121] (Air blow test) For the insulation materials according to each example, the first and second surfaces of the insulation materials were used as the evaluation surfaces, and an air blow test was performed using an apparatus as shown in FIG. 5. Specifically, the insulation material 1 was sandwiched between two stainless steel plates 62, 62 having a square opening 62a of 20 mm square in the center, and the insulation material 1 was held in a position in which the surface direction was approximately vertical. Air (pressure: 0.18 MPa) at a flow rate of 940 L / min was blown from a nozzle 66 with a diameter of 6 mm for 60 seconds from a position 10 mm in the normal direction of the evaluation surface side to the insulation material 1 exposed from the opening 62a. If no through holes were formed in the layer constituting the evaluation surface, the wind pressure resistance was evaluated as "○" (passed), and if a through hole was formed, it was evaluated as "×" (failed). The results are shown in Table 1. In the above burner test and air blow test, in the insulation materials of Examples 1 to 5 and 8 to 10, the surface on the insulation layer side was designated as the first side, and the surface on the buffer layer side was designated as the second side, and in Examples 6 and 7, which had a single-layer structure, one side and the other side of the insulation material were designated as the first side and the second side.
[0122] (Burst resistance) In the burner test, if the evaluation result was "○" for both the first side (insulation layer side) and the second side (buffer layer side) as the evaluation target side, and if the evaluation result was "○" for both the first side (insulation layer side) and the second side (buffer layer side) as the evaluation target side in the air blow test, the burst resistance was evaluated as "good". If the evaluation result for either the first side or the second side in either the burner test or the air blow test was "×", the burst resistance was evaluated as "poor". The results are shown in Table 1.
[0123] [Table 1]
[0124] As shown in Table 1, the insulating materials of Examples 1 to 5, which include a heat insulating layer and a buffer layer and have a first surface (surface on the heat insulating layer side) and a second surface (surface on the buffer layer side) that both have flame resistance that passes the burner test, exhibited good wind pressure resistance on both the first and second surfaces and were excellent in burst resistance. B It was confirmed that even when the temperature was changed to 800°C, 1000°C, and 1200°C, both the first and second sides exhibited flame resistance that passed the burner test. On the other hand, the insulating materials of Examples 6 and 7, which consisted of only a heat insulating layer, lacked a balance between flame resistance and wind pressure resistance. Also, the insulating materials of Examples 8 to 10 had insufficient flame resistance on the surface on the buffer layer side.
[0125] Although specific examples of the present invention have been described in detail above, these are merely examples and do not limit the scope of the claims. The technology described in the claims includes various modifications and changes of the specific examples exemplified above. [Explanation of symbols]
[0126] 1. Insulation 10. Insulation Layer 20 Buffer layer 30 Covering material 31A Resin film 31B Resin film 32 Seal part 33 Vent 34 Breathable membrane 40 Insulation with coating 50 Battery Module 51 Battery Cell 61 Thermocouple 62 Stainless steel plate 62a aperture 63 Burner 66 Nozzle
Claims
1. A thermal insulation material including a thermal insulation layer and a buffer layer, The thermal insulation layer includes silica particles, The buffer layer is a fiber molded body mainly composed of inorganic fibers, the heat insulating material is in a sheet shape having a first surface and a second surface, the first surface and the second surface each being constituted by the heat insulating layer or the buffer layer, The insulating material has flame resistance that is evaluated as passing in the following burner test, regardless of whether the first surface or the second surface is the surface to be evaluated. [Burner test] The surface to be evaluated of the insulating material is heated at 750° C. for 2 minutes using a burner, and if no through holes are formed in the layer that constitutes the surface to be evaluated, it is rated as "passed."
2. The heat insulating material according to claim 1 , wherein one of the first surface and the second surface is constituted by the heat insulating layer, and the other surface is constituted by the buffer layer.
3. The insulating layer according to claim 1 or 2, wherein the insulating material has wind pressure resistance that is evaluated as passing in the following air blow test, regardless of whether the first surface or the second surface is the surface to be evaluated. [Air blow test] Air at a flow rate of 940 L / min is sprayed from a nozzle with a diameter of 6 mm for 60 seconds from a position 10 mm in the normal direction of the surface of the insulation being evaluated, and if no through holes are formed in the layer that makes up the surface being evaluated, it is rated as "passed."
4. The insulation material according to claim 1 or 2, wherein the insulating layer contains fumed silica as the silica particles.
5. 3. The heat insulating material according to claim 1, wherein in the buffer layer, the inorganic fibers contain, as a main component, one or more fibers selected from the group consisting of alkaline earth silicate fibers, silica-alumina ceramic fibers, and alumina fibers.
6. The insulating material according to claim 1 or 2, wherein the initial thickness of the insulating material is 5 mm or less.
7. The heat insulating material according to claim 1 or 2, wherein the heat insulating material has a compressive deformation rate of 10% or more at a compressive stress of 0.4 MPa.
8. 3. The heat insulating material according to claim 1, which is covered with a covering material made of a resin film.
9. The heat insulating material according to claim 1 or 2, which is used by being disposed between adjacent cells of a battery module or a battery pack including a plurality of arranged cells.
Citation Information
Patent Citations
Heat insulation sheet for battery pack and battery pack
JP2021034278A
Thermally insulating material for battery, and non-aqueous electrolyte secondary battery
WO2023054411A1